Surface modified copper current collector, preparation method and application thereof
By forming a copper oxide/cubous oxide thin film modification layer on the lithium battery current collector, the dendrite problem in lithium battery is solved, the cycle life and safety performance of the battery are improved, and higher energy density and better battery are achieved stability.
Patent Information
- Application Number
- CN202311048259.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
AI Technical Summary
There are dendrite problems in lithium batteries, resulting in a decrease in battery circulation performance and an increase in safety risks. The existing current collector modification methods are complex and difficult to control.
By coating the copper salt solution on the copper foil to form a uniform liquid film and reacting under the ultraviolet lamp, a copper oxide/cubous oxide thin film modified layer is formed, which simplifies the process flow and improves the controllability of the modified layer.
This method improves the cycle life and safety performance of lithium batteries, provides higher energy density and better battery stability, and is simple in process and low in cost.
Smart Images

Figure BDA0004403390870000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery preparation, and in particular relates to a copper oxide thin film modified negative electrode current collector, a preparation method and application thereof in lithium ion batteries and lithium sulfur batteries. Background Art
[0002] Lithium secondary batteries have been widely used in commercial applications since the 1990s and have become an indispensable necessity in daily life. Lithium-ion batteries can be seen everywhere in life, including large-scale fixed energy storage, mobile energy storage, and portable 3C products. In modern society, as the market share of electric vehicles continues to rise, people's demand for energy density is getting higher and higher. Lithium metal batteries (LMBs) have also appeared in people's field of vision because their energy density is much higher than that of graphite anode lithium batteries. However, in the endless battery safety news, battery safety has gradually been pushed to the forefront, and the cycle performance and overall safety performance of lithium secondary batteries have become important research directions.
[0003] The lithium dendrite problem is one of the biggest culprits causing lithium battery safety issues. In traditional current collectors, local charge enrichment leads to uneven nucleation and deposition of lithium. Therefore, during the battery cycle, the excess lithium metal deposited on the negative electrode tends to concentrate locally, forming dendritic growth, and the tip effect of the dendrite further exacerbates this process. This problem not only reduces the battery cycle performance, but also increases the risk of battery short circuit.
[0004] On the negative electrode side of lithium batteries where dendrite problems are concentrated, copper foil has been widely used as a traditional current collector due to its good conductivity, ductility and stability. However, flat copper foil itself has an extremely low specific surface area and low lithium storage capacity. Its microscopic surface structure (covered with cracks and protrusions) leads to uneven distribution of charge and deposition sites on the surface of the current collector, which can easily aggravate battery safety issues. Therefore, surface modification of the current collector has always been the direction pursued by many scholars.
[0005] Structural modification and chemical modification are the mainstream modification directions of current collectors. The former changes the surface physical structure of copper foil by surface etching, while the latter controls the deposition of lithium by coating, alloying and other means. However, the existing methods are often more complicated in terms of process, and it is difficult to control the area and depth of modification, which damages the mechanical properties of the current collector. CN111600036A
[0006] The copper foil surface is etched with sodium hydroxide and ammonium thiosulfate solution to form three-dimensional porous copper oxide, but the etching depth is difficult to control and mechanical damage is caused to the foil itself; CN113036071A uses metal oxides and alkali metal salts to react at high temperature to generate nitride modification, which takes a long time and involves high-temperature equipment, and the overall process cost is high. People are in urgent need of exploring a simple and low-cost current collector modification method. Summary of the invention
[0007] The purpose of the present invention is to provide a current collector surface modified by copper oxide / cuprous oxide film and a preparation method thereof, and to apply it to the field of lithium ion batteries / lithium metal batteries to improve the cycle life and safety performance of the battery.
[0008] In order to achieve the above technical effects, the technical solution adopted by the present invention is as follows:
[0009] In one aspect, the present invention provides a method for preparing a surface-modified copper current collector, comprising the following steps:
[0010] (1) dissolving a soluble copper salt in a solvent to obtain a solution A;
[0011] (2) coating solution A on copper foil to form a uniform liquid film;
[0012] (3) removing the foil material covered with the liquid film and placing it under an ultraviolet lamp for light reaction to obtain a copper foil current collector covered with the film;
[0013] (4) The obtained coated copper foil current collector is cleaned and dried to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
[0014] In the present invention, the soluble copper salt in step (1) is selected from copper sulfate, copper chloride, copper nitrate, preferably copper sulfate; the solvent is not particularly limited, and an organic solvent or water, such as alcohols, esters, and furan solvents, can be selected. From the perspective of economic cost and difficulty of volatilization, water, such as deionized water, is preferred. The concentration of the solution A is not particularly limited, and is preferably 0.1wt% to 10wt%, and more preferably 0.1wt% to 5wt%.
[0015] In the present invention, the amount of solution A added in step (2) is 5 to 100 μL / cm 2 Copper foil, preferably 10 to 50 μL / cm 2 Copper foil.
[0016] In the present invention, the coating method in step (2) can be selected from conventional methods in the art, such as rubbing, spraying, brushing, cast coating, spin coating, etc., preferably spin coating.
[0017] In the present invention, the spin coating method is as follows: copper foil is covered on the surface of a spin coater, solution A is dripped onto the center of the foil, the spin coater is started for spin coating, and the spin coating is repeated until the solution covers the entire foil.
[0018] In the present invention, the rotation rate of the spin coater is 500rpm-2000rpm, the single rotation time is 10-30s, and the spin coating step is repeated 3 to 10 times.
[0019] In the present invention, the power of the ultraviolet lamp in step (3) is not particularly limited as long as it can trigger the reaction, preferably 1-50W, more preferably 5-10W, the wavelength of the ultraviolet lamp is 185nm-365nm, and the reaction time is 5-200min, preferably 10min-120min.
[0020] In the present invention, the cleaning solvent in step (4) is not particularly limited, and is preferably deionized water. The drying temperature and time can be conventionally adjusted according to the drying rate and degree of drying. Preferably, the drying temperature is 20-80°C and the drying time is 1-6h.
[0021] On the other hand, the present invention also provides a modified copper current collector prepared by the above method, wherein the modified copper current collector comprises a copper oxide / cuprous oxide thin film modified layer, and the thickness of the modified layer is between 0.05 μm and 50 μm.
[0022] Finally, the present invention also provides the application of the modified copper current collector in the negative electrode loading of a lithium battery.
[0023] The positive effects of the present invention are:
[0024] The present invention applies a modified coating on the surface of a traditional current collector through a simple coating process and an ultraviolet irradiation process. The process flow is simple and controllable, without heating or corrosion processes. The modified layer is controlled by the solution concentration and the number of coatings, and can reach a nanometer-level thickness. It is applied to different lithium-ion batteries and lithium metal batteries, and has great industrial prospects. At the same time, the raw materials used for modification are inexpensive and cost-effective, and copper oxide / cuprous oxide is stable on the surface of copper foil, and will not affect the negative electrode potential and battery voltage. The battery operation process is safe and reliable. Copper oxide / cuprous oxide provides a large number of lithium-philic active sites on the surface, which is conducive to the uniform nucleation and deposition of lithium ions. The pores and defects naturally formed during the oxidation process provide a large amount of lithium storage space. The entire current collector modification process enables the traditional current collector to provide a higher cycle life, better safety performance and energy density improvement in lithium batteries. DETAILED DESCRIPTION
[0025] Raw materials and sources:
[0026] Anhydrous Copper Sulfate, AR, 99.0%, Aladdin
[0027] Cupric chloride anhydrous, 98%, Aladdin
[0028] Copper Nitrate Trihydrate, 99%, Aladdin
[0029] The electrolyte ZL-002 was purchased from Tianci Materials
[0030] Lithium-ion button cell preparation:
[0031] The method comprises the following steps: commercial graphite, Super P and LA133 are fully ground in water at a mass ratio of 90:6:4, and then coated on the surface of the current collector of the embodiment and the comparative example and dried to obtain a negative electrode sheet. The electrode sheet is cut into a 12 mm diameter disc, and metallic lithium is used as a counter electrode. In a glove box filled with argon, a diaphragm (PP / PE, Celgard 2400), an electrolyte (Tianci) and a CR2032 button battery shell are assembled into a button battery for standby use.
[0032] Lithium metal symmetric battery preparation:
[0033] The process comprises the following steps: cutting the modified current collector into 12 mm diameter discs, using metallic lithium as the counter electrode, assembling a button cell with a separator, an electrolyte and a CR2032 button cell shell in an argon-filled glove box, and discharging and depositing 6 mAh / cm at the negative electrode using a Xinwei battery device. 2 The metallic lithium is set aside.
[0034] Test method:
[0035] (1) Symmetrical battery test method: After cyclic activation five times with a current of 50 μA between 0.1 and 1.5 V, the battery was tested with a current of 2 mAh / cm 2 Carry out charge and discharge tests of equal duration at a current density of 10000 rpm until the current fails, and record the cycle time.
[0036] (2) Lithium-ion battery test method: The battery is charged and discharged with a current of 1A in the voltage range of 0.1-1.5V, and its capacity, coulombic efficiency and capacity retention after 50 cycles are recorded.
[0037] Calculation of capacity retention rate: R = C1 / C2*100%
[0038] Where: R – capacity retention rate; C1 – discharge capacity after 50 cycles; C2 – discharge capacity in the first cycle.
[0039] Example 1
[0040] (1) dissolving 1 g of copper sulfate in 99 g of deionized water to obtain a 1 wt% copper sulfate solution;
[0041] (2) Copper foil was covered on the surface of the spin coater, and 0.3 mL of 1 wt% copper sulfate solution was added dropwise to 10 x 10
[0042] cm foil center;
[0043] (3) Start the spin coater and spin coat at a speed of 1500 rpm for 30 s. Repeat the spin coating three times.
[0044] (4) The foil covered with the copper sulfate film was removed and placed under a 10 W, 185 nm ultraviolet lamp in an air atmosphere for 30 minutes to obtain a dry coated copper foil current collector.
[0045] (5) The obtained current collector is washed with deionized water and dried at 50° C. for 3 h to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
[0046] The copper current collector modified by copper oxide / cuprous oxide thin film was photographed by scanning electron microscope, and the thickness of the modified layer was measured to be 0.5 μm. According to the above method, the copper current collector modified by copper oxide / cuprous oxide thin film was prepared into lithium metal symmetric battery and lithium ion battery, and their electrochemical performance was measured. The data are shown in Table 1.
[0047] Example 2
[0048] (1) dissolving 5 g of copper sulfate in 95 g of deionized water to obtain a 5 wt % copper sulfate solution;
[0049] (2) Copper foil was covered on the surface of the spin coater, and 0.5 mL of 5 wt% copper sulfate solution was added dropwise to the 10 x 10
[0050] cm foil center;
[0051] (3) Start the spin coater and spin coat at a speed of 2000 rpm for 30 s. Repeat the spin coating 10 times.
[0052] (4) The foil covered with the copper sulfate film was removed and placed under a 9W, 365nm ultraviolet lamp in an air atmosphere for 120 minutes to obtain a dry coated copper foil current collector.
[0053] (5) The obtained current collector is washed with deionized water and dried at 50° C. for 3 h to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
[0054] The copper current collector modified by copper oxide / cuprous oxide thin film was photographed by scanning electron microscope, and the thickness of the modified layer was measured to be 30 μm. According to the above method, the copper current collector modified by copper oxide / cuprous oxide thin film was prepared into lithium metal symmetric battery and lithium ion battery, and their electrochemical performance was measured. The data are shown in Table 1.
[0055] Example 3
[0056] (1) dissolving 3 g of copper chloride in 97 g of deionized water to obtain a 3 wt % copper sulfate solution;
[0057] (2) Copper foil was covered on the surface of the spin coater, and 0.5 mL of 3 wt% copper sulfate solution was added dropwise on 10 x 10
[0058] cm foil center;
[0059] (3) Start the spin coater and spin coat at a speed of 2000 rpm for 15 s. Repeat the spin coating 5 times.
[0060] (4) The foil covered with the copper chloride film was removed and placed under a 6W, 254nm ultraviolet lamp in an air atmosphere for 60 minutes to obtain a dry coated copper foil current collector.
[0061] (5) The obtained current collector is washed with deionized water and dried at 50° C. for 3 h to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
[0062] The copper current collector modified by copper oxide / cuprous oxide thin film was photographed by scanning electron microscope, and the thickness of the modified layer was measured to be 5 μm. According to the above method, the copper current collector modified by copper oxide / cuprous oxide thin film was prepared into lithium metal symmetric battery and lithium ion battery, and their electrochemical performance was measured. The data are shown in Table 1.
[0063] Example 4
[0064] (1) dissolving 0.1 g of copper nitrate in 99.9 g of deionized water to obtain a 0.1 wt% copper sulfate solution;
[0065] (2) Copper foil was placed on the surface of the spin coater, and 0.1 mL of 0.1 wt% copper sulfate solution was added dropwise to the 10x
[0066] 10cm foil center;
[0067] (3) Start the spin coater and spin coat at a speed of 500 rpm for 10 s. Repeat the spin coating three times.
[0068] (4) The foil covered with the copper sulfate film was removed and placed under a 10 W, 185 nm ultraviolet lamp in an air atmosphere for 10 min to obtain a dry coated copper foil current collector.
[0069] (5) The obtained current collector is washed with deionized water and dried at 50° C. for 3 h to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
[0070] The copper current collector modified by copper oxide / cuprous oxide thin film was photographed by scanning electron microscope, and the thickness of the modified layer was measured to be 0.1 μm. According to the above method, the copper current collector modified by copper oxide / cuprous oxide thin film was prepared into lithium metal symmetric battery and lithium ion battery, and their electrochemical performance was measured. The data are shown in Table 1.
[0071] Comparative Example 1
[0072] The unmodified copper current collector was prepared into lithium metal symmetric batteries and lithium ion batteries, respectively, and their electrochemical performances were measured. The data are shown in Table 1.
[0073] Comparative Example 2
[0074] The ultraviolet irradiation step in step (4) of Example 1 was changed to standing in air for 30 minutes. The obtained material was used as Comparative Example 2. A lithium metal symmetric battery and a lithium ion battery were prepared according to the above method, and their electrochemical properties were measured. The data are shown in Table 1.
[0075] Comparative Example 3
[0076] Commercial copper oxide (99.99%, Aladdin) and LA133 were uniformly mixed in a ratio of 95:5, coated on the surface of copper foil using a 50 μm scraper, and then dried and tested accordingly.
[0077]
[0078] Table 1 Electrochemical performance of each embodiment and comparative example
[0079] From the performance display in Table 1, it can be seen that in the symmetrical battery test of lithium metal negative electrode, the symmetrical battery prepared by the modified current collector can fail after 700-1000 hours of cycling, while the unmodified copper foil can only last about 200 hours. In the lithium-ion battery test, although commercial graphite has good stability, the modified current collector still shows advantages in coulomb efficiency and cycle retention rate. In the actual application of the battery, the battery can be used for far more than 50 cycles, which has good advantages in long-term applications.
Claims
1. A method for preparing a surface-modified copper current collector, comprising the following steps: (1) dissolving a soluble copper salt in a solvent to obtain a solution A; (2) coating solution A on copper foil to form a uniform liquid film; (3) removing the foil material covered with the liquid film and placing it under an ultraviolet lamp for light reaction to obtain a copper foil current collector covered with the film; (4) The obtained coated copper foil current collector is cleaned and dried to obtain a copper oxide / cuprous oxide thin film modified copper current collector.
2. The preparation method according to claim 1, characterized in that In step (1), the soluble copper salt is selected from copper sulfate, copper chloride, copper nitrate, preferably copper sulfate; and / or, the solvent is selected from an organic solvent or water, preferably water; and / or, the concentration of solution A is 0.1wt% to 10wt%, preferably 0.1wt% to 5wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The amount of solution A added in step (2) is 5 to 100 μL / cm 2 Copper foil, preferably 10 to 50 μL / cm 2 Copper foil.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The coating method in step (2) is selected from wiping, spraying, brushing, cast coating, and spin coating, preferably spin coating.
5. The preparation method according to claim 4, characterized in that: The spin coating method is as follows: copper foil is covered on the surface of a spin coater, solution A is dripped onto the center of the foil, the spin coater is started for spin coating, and the spin coating is repeated until the solution covers the entire foil.
6. The preparation method according to claim 5, characterized in that: The rotation rate of the spin coater is 500 rpm-2000 rpm, the single rotation time is 10-30 s, and the spin coating step is repeated 3 to 10 times.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The power of the ultraviolet lamp in step (3) is 1-50W, more preferably 5-10W, the wavelength of the ultraviolet lamp is 185nm-365nm, and the reaction time is 5-200min, preferably 10min-120min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The cleaning solvent in step (4) is preferably deionized water, the drying temperature is 20-80° C., and the drying time is 1-6 h.
9. The modified copper current collector prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The modified copper current collector comprises a copper oxide / cuprous oxide thin film modified layer, and the thickness of the modified layer is between 0.05 μm and 50 μm.
10. Use of the modified copper current collector prepared by the preparation method according to any one of claims 1 to 8 or the modified copper current collector according to claim 9 in negative electrode loading of a lithium battery.
Citation Information
Patent Citations
Three-dimensional porous copper oxide modified copper foil for lithium metal battery current collector as well as preparation method and application thereof
CN111600036A
Current collector modification method, and modified current collector and application thereof
CN113036071A